Clinicopathologic study of odontogenic keratocysts in Singapore and Malaysia - Ngeow, Wei Cheong; Zain, R.B.; Yeo, J.F.; Chai, W.L. (AMER ASSOC DENTAL RESEARCH, 1999)
A retrospective study of odontogenic keratocysts in the Malaysia-Singapore region was done. The purpose of this study is to present the clinicopathological features of odontogenic keratocysts in the Oriental population and to compare the data with those from other reported studies. Biopsy records from 1981 to 1992 of 61 cases of odontogenic keratocysts in Malaysia and Singapore showed that there were 42.6% female and 57.4% male patients. The cysts occurred in 75.4% Chinese, 6.6% Malays, 9.8% Indian, and 8.2% other ethnic groups. The mean age of these patients was 26.98 ± 15.38 years with peak incidence in the second to fourth decades. The location of the lesion was more often in the mandible (65.5%) than the maxilla (31.0%). There is marked predilection for the posterior mandible. Odontogenic keratocysts presenting at the site of dentigerous a cyst was observed in 7 cases (11.5%). Histologically, 90.2% of the cyst were lined by parakeratinised stratified squamous epithelium while only 3.3% of the cyst with orthokeratinised stratified squamous epithelium. Mixed parakeratinised and orthokeratinised epithelial lining was observed in 4 cases (6.5%). Inflammation of cyst wall was found in 42 cases (68.8%). Stellate-like inflamed lining epithelium was observed in 9.8% of the cases while 6.6% of the cases demonstrated Rushton bodies in the epithelial lining. Keratin in the lumen was observed in 19.7% of the cases. Satellite cyst was observed in only 6 cases (9.8%). In conclusion, most clinical and histological features seen in this study similar to that for the Caucasian. The only clinical feature that differs is the peak incidence which ranged from the second to fourth decades with an absence of the second peak for our study